2021
DOI: 10.1186/s12872-021-01954-2
|View full text |Cite
|
Sign up to set email alerts
|

Chinese patients’ clinical and psychosocial outcomes in the 6 months following percutaneous coronary intervention

Abstract: Background In China, there has been a precipitous increase in the number of percutaneous coronary interventions (PCI) conducted. We sought to characterize the clinical and psychosocial trajectory of PCI patients from the time of procedure through 6 months post, and correlates of adverse cardiovascular events (ACEs). Methods In this prospective, observational study, patients from 2 hospitals in Shanghai, China were assessed. At follow-up visits at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 3 The diagnosis of post-PCI depressive symptoms is a dynamic process, with different manifestations in different time stages, and the conclusions of different studies are quite different, which may be related to the timing of post-PCI depressive symptoms determination, psychological assessment methods, and different criteria for evaluation. 24 The gensini scores reflect the severity of coronary artery stenosis. Our results showed that gensini scores were risk factors for the development of post-PCI depressive symptoms, which was broadly consistent with the recent studies.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The diagnosis of post-PCI depressive symptoms is a dynamic process, with different manifestations in different time stages, and the conclusions of different studies are quite different, which may be related to the timing of post-PCI depressive symptoms determination, psychological assessment methods, and different criteria for evaluation. 24 The gensini scores reflect the severity of coronary artery stenosis. Our results showed that gensini scores were risk factors for the development of post-PCI depressive symptoms, which was broadly consistent with the recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…The HADS score is derived using a validated questionnaire and is widely used within CR to assess cardiac patients’ level of anxiety and depression 29 30. The Barthel index is used for assessment of performance in basic activities of daily living 31–33. The CFS is a clinical judgement-based frailty tool and is widely used in the assessment of cardiac patients 24 34…”
Section: Methodsmentioning
confidence: 99%
“…29 30 The Barthel index is used for assessment of performance in basic activities of daily living. [31][32][33] The CFS is a clinical judgement-based frailty tool and is widely used in the assessment of cardiac patients. 24 34 The participant's medical notes will be used to collect a full medical history and information, including their sex and date of birth.…”
Section: Baseline Visitmentioning
confidence: 99%
“…Yang [16] investigated post-PCI patients with CHD in three hospitals in Changsha, and found that the incidence rate of post-PCI patients harboring negative emotions (including depression, anxiety, and irritability) was 63.8%, with depression being the highest at 39.6%. A 6-month longitudinal observational study [17] found that more than half of post-PCI patients experienced constant anxiety and depression for 6 months. Furthermore, the depression gradually worsened over time and adversely affected the prognosis.…”
Section: Current Situation Of Depression After Pci Domesticallymentioning
confidence: 99%